The Role of Wisteria Floribunda (M2BPGi) Serum Level for Diagnosing Liver Fibrosis in Hepatitis B Patient: An Evidence Based Case Report - Yosafat Lambang Prasetyadi; Agnes Elsha Maria Simbolon; Anggi Anggelina Permatasari; Dela Ryana Swaraghani; Shafira Chairunisa; Juferdy Kurniawan (The Indonesian Society for Digestive Endoscopy, 2019)
Aim: To assess M2BPGi serum performance compared to liver biopsy in diagnosisng liver fibrosisMethod: Literature search using Pubmed®, Ebsco®, ProQuest®, Scopus®, Clinical Key databases, and the Cochrane Library® yield four relevant and full-text articles. The four articles were critically appraised for its validity, importance, and applicability.Results: Sensitivity and specificity in all four studies showed that M2BPGi serum was inadequate to ruling in and ruling out the diagnosis of liver fibrosis in chronic hepatitis B patients. The difference in M2BPGi cut-off value to determine the stage of fibrosis in each study makes this value cannot be used as an accurate standard to determine the advanced stage (F≥3) of liver fibrosis. On the other hand, M2BPGi serum combined with other tests are known to improve the diagnostic accuracy.Conclusion: MBP2Gi serum cannot be used as a diagnostic modality for detecting liver fibrosis in chronic hepatitis B patients.